2014
DOI: 10.14740/jocmr1889w
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sitagliptin on Lipid Profile in Patients With Type 2 Diabetes Mellitus

Abstract: BackgroundAnimal studies have demonstrated that an inhibition of DPP-4 has an impact on the secretion of cholesterol and apoB by the small intestine. However, there is no consensus about the changes of the lipid profile following administration of sitagliptin.MethodsAccordingly, we treated patients who had type 2 diabetes complicated by dyslipidemia with sitagliptin and evaluated its effects on the profile of lipid parameters. A total of 248 outpatients with type 2 diabetes complicated by dyslipidemia were tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 29 publications
3
23
1
Order By: Relevance
“…In the present study, sitagliptin did not cause any increase in the body mass index. Sitagliptin also decreases postprandial triglyceride level [27] and lowers blood pressure, blood lipid level [28] and alkaline phosphatase level [29]. Our present study also showed decreased systolic and diastolic blood pressures, decreased LDL-C level and decreased triglyceride levels, which is similar to results from previously published studies.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, sitagliptin did not cause any increase in the body mass index. Sitagliptin also decreases postprandial triglyceride level [27] and lowers blood pressure, blood lipid level [28] and alkaline phosphatase level [29]. Our present study also showed decreased systolic and diastolic blood pressures, decreased LDL-C level and decreased triglyceride levels, which is similar to results from previously published studies.…”
Section: Discussionsupporting
confidence: 91%
“…In addition to their effect of improving glycemic control, DPP‐4 inhibitors have recently also been reported to exert extrapancreatic actions, including ameliorating the risk of diabetic complications, such as nephropathy, retinopathy and neuropathy, and also the risk of cardiovascular disease. Several previously published studies, including a meta‐analysis, have also reported the lipid‐lowering effect of DPP‐4 inhibitors. Two meta‐analyses have shown that DPP‐4 inhibitors, such as sitagliptin, vildagliptin, alogliptin, saxagliptin and linagliptin, reduce both the serum cholesterol and serum triglyceride levels.…”
Section: Introductionmentioning
confidence: 99%
“…[10] had revealed changes of the lipid profile after Sitagliptin treatment, the HDL level & Triglyceride level were not significantly (p>0.05) reduced after 12 weeks of Sitagliptin treatment from baseline.…”
Section: Resultsmentioning
confidence: 89%